The narrative speech event: the narrator and the dual voice - Beltrán Almería, Luis (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
The pragmatic turn of the Linguistics can offer progress in the theory of literary language. For it, the categories of the speech event subject and the subject of consciousness are revised. A dialogic conception of speech event and its subjects is outlined as contrasted with the conception of two categories in K. Hamburger and É. Benveniste, among others. The proposed revision of the categories narrator and dual voice in the narration is based on this dialogic conception.